Fatique behavior of steel carbonizing on high humidity environment - Nasution, Muslih; Yusmartato, Y; Parinduri, Luthfi; Bakhori Nasution, Akhmad; Hasibuan, Abdurrozzaq (International Journal of Engineering and Technology, 2018)
Carbonizing is an attempt to improve the mechanical properties of steel carbon is added from the outside by placing the steel in a box, then the carbon is sown by heating above the critical temperature. Because of the heating process, the bonds of the steel atoms will stretch to each other, in the presence of the pressure of barium carbonate, the carbon diffuses into the steel through the distance between the atoms of the steel atoms, and then heated through the environment air, so that the structure of the microstructure consists of a ferrite layer and pearlite with a thicker carbon content on the outer shell. The diffusing carbon increases as the warming temperature is carried out, using a rotating bending fatigue type machine at 887.5 rpm, the steel is tested fatally until it is broken. The fatigue conditions were performed with the S-N curve. The exper-iments were carried out on krupp 1191 heated steels at 8000C, 9000C and 10000C, respectively, and then performed a fa-tigue test on RH70%, RH80% and RH90% environments. After the observation that the thicker the carbon layer formed the higher the fatigue strength. However, in a high humidity environment the fatigue strength decreases as the moisture of the test environment increases.Â